Personality types of accountants / Wan Mardyatul Miza Wan Tahir and Ja'izah Abdul Jabar - Wan Tahir, Wan Mardyatul Miza; Abdul Jabar, Ja'izah (Universiti Teknologi MARA, Negeri Sembilan, 2022)
According to Psychologist Carl Jung, there are 16 personality types among humans. The Jung personality test measures human behaviour on preferences for dealing with and relating to people, processing information, making decisions, and organizing their life. The Australian Bureau of Statistics describes the professional profiling and characteristic personality qualities of Accountants and those in the Financial Sectors that match 6 of Jung's 16 personality types. They are ESTJ, ESFJ, ISTJ, ISFJ, ENFJ and ENFP. Interestingly, 4 out of 6 types of personality start with the letter E which represents the extrovert type. This makes sense since nowadays an accountant needs to be able to socialize with clients and even co-workers. The table below shows the main characteristics of the 6 personality types that match accountant traits: The ESTJ has personality type which are good qualities for an accountant. In addition, they rely more heavily on facts than theories and are consistent and observant. While ESFJ are typically very compliant, and this natural desire to adhere to rules and traditions is an asset working as an accountant. On the other hand, ISTJ personality types are significant traits for accountants, who should be responsible and trustworthy. The ISFJ personality type has introverted sensing and thinking functions yet diligently serves others. Next ENFJ personality types are considered the "mentors" and their communication skills leading others to success provide great potential for ENFJs to thrive in a leadership position in the accounting field. Finally, the ENFP personality types are called "advocates" and make positive contributions in their careers.